Systolic blood pressure and risk of valvular heart disease: a mendelian randomization study - Nazarzadeh, M; Pinho-Gomes, A; Smith Byrne, K; Canoy, D; Raimondi, F; Ayala Solares, J; Otto, C; Rahimi, K (American Medical Association, 2019)
Importance Modifiable risk factors for valvular heart disease remain largely unknown, which limits prevention and treatment. Objective To assess the association between systolic blood pressure (BP) and major valvular heart disease. Design, Setting, and Participants A UK Biobank population-based cohort of 502 602 men and women aged 40 to 96 years at baseline was evaluated through mendelian randomization using individual participant data. Inclusion criteria were valid genetic data and BP measurements. The participants were recruited between 2006 and 2010; data analysis was performed from June 2018 to January 2019. Exposures Systolic BP was measured during clinical assessment and instruments for the genetic effect of high BP were identified from variants that were independently (linkage disequilibrium threshold of r2<0.1) associated with systolic BP with minor allele frequency greater than 0.01. A total of 130 single-nucleotide polymorphisms that have been shown to be associated with systolic BP in a genome-wide association meta-analysis involving 1 million participants of European ancestry were selected. Main Outcomes and Measures Incident aortic stenosis, aortic regurgitation, and mitral regurgitation, individually and combined. Cases were largely based on hospital records linked to the UK Biobank with International Classification of Diseases and Health Related Problems, Tenth Revision codes. Results Of the 502 602 individuals screened, 329 237 participants (177 741 [53.99%] women; mean [SD] age, 56.93 [7.99] years) had valid genetic data and BP measurements; of this cohort, 3570 individuals (1.08%) had a diagnosis of valvular heart disease (aortic stenosis, 1491 [0.45%]; aortic regurgitation, 634 [0.19%]; and mitral regurgitation, 1736 [0.53%]). Each genetically associated 20–mm Hg increment in systolic BP was associated with an increased risk of aortic stenosis (odds ratio [OR], 3.26; 95% CI, 1.50-7.10), aortic regurgitation (OR, 2.59; 95% CI, 0.75-8.92), and mitral regurgitation (OR, 2.19; 95% CI, 1.07-4.47), with no evidence for heterogeneity by type of valvular heart disease (P = .90). Sensitivity analyses confirmed the robustness of the association. Conclusions and Relevance Lifetime exposure to elevated systolic BP appears to be associated with an increased risk of major valvular heart disease.